2004
DOI: 10.1093/glycob/cwh128
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a heparin with high anticoagulant activity from the clam Tapes phylippinarum: evidence for the presence of a high content of antithrombin III binding site

Abstract: Heparin with high anticoagulant activity (activated partial thromboplastin time of 347 +/- 56.4 and anti-Xa activity of 317 +/- 48.3) was isolated from the marine clam species Tapes phylippinarum in an amount of approximately 2.1 mg/g dry animals. Agarose-gel electrophoresis showed a high content of the slow-moving heparin component (22 +/- 6.8%) and 78 +/- 5.4% of the fast-moving species. An average molecular mass of 13,600 was calculated by PAGE analysis, whereas a number average molecular weight Mn value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 35 publications
4
51
0
Order By: Relevance
“…The significance of high levels of disaccharides with free amino groups in HS from these species is not known, but may signal the existence of an evolutionarily ancient class of biologically important functional motifs. Earlier studies have shown that GAGs are expressed in several other invertebrates (37,47,48). While the earliest diverging animal phylum, Porifera (sponges) appears to express only CS, the expression of both CS and HS is manifest throughout the rest of the animal kingdom (37).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of high levels of disaccharides with free amino groups in HS from these species is not known, but may signal the existence of an evolutionarily ancient class of biologically important functional motifs. Earlier studies have shown that GAGs are expressed in several other invertebrates (37,47,48). While the earliest diverging animal phylum, Porifera (sponges) appears to express only CS, the expression of both CS and HS is manifest throughout the rest of the animal kingdom (37).…”
Section: Discussionmentioning
confidence: 99%
“…Heparin and heparan sulfate (HS) GAGs bind over 100 different proteins, including enzymes, protease inhibitors, lipoproteins, growth factors, chemokines, selectins, extracellular matrix proteins, receptor proteins, viral coat proteins and nuclear proteins (Linhardt and Toida, 2004;Capila and Linhardt, 2002). Heparin and HS are closely related, overlapping structures that are widely distributed in invertebrates (Medeiros et al, 2000;Nobuo, 2003;Cesaretti et al, 2004), as well as in vertebrates (Gomes and Dietrich, 1982). Moreover, HS GAGs modulate many biological activities including signal transduction (Ibrahimi et al, 2005), inflammation (Peterson et al, 2004), complement activation (Yu et al, 2005) and cAMP-dependent substrate phosphorylation catalyzed by protein kinase (Dittmann et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to have a detailed understanding of heparin/HS structure to develop structure activity relationships. Much research has been performed to determine the structure of heparin/HS isolated different species and tissues (Gomes and Dietrich, 1982;Medeiros et al, 2000;Nobuo, 2003;Cesaretti et al, 2004). Despite these efforts, there still remains the question about how the fine structure of the GAG moiety of these HSPGs regulates their biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…The proteoglycans chondroitin sulfate and heparan sulfate, as well as the structurally related heparin (31), have been observed in a wide variety of animals, ranging from mammals (3-6, 32, 33), to birds (34), clams (35), fruit flies, and worms (24). Nothing, however, is known about these molecules in insects of medical importance, where they may play a role in the transmission of pathogens.…”
Section: Discussionmentioning
confidence: 99%